A high thermal conductivity Al-Si based alloy material and preparation method thereof
By adding specific elements to the Al-Si-based alloy and performing optimized heat treatment, the inverted relationship between the thermal conductivity and mechanical properties of the existing Al-Si-based alloy materials is solved, and the preparation of alloy materials with high thermal conductivity and excellent mechanical properties is achieved. Meets the needs of high-end electronic communication and other fields.
Patent Information
- Application Number
- CN202411244302.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-06
AI Technical Summary
There is an inverted relationship between thermal conductivity and mechanical properties of existing Al-Si-based alloy materials, and the preparation process is complex and low efficiency, making it difficult to meet the demand for high-thermal conductivity materials in high-end electronic communication and other fields.
The thermal conductivity and mechanical properties of the alloy are improved by adding strontium, boron, rare earth elements lanthanum and cerium to the Al-Si-based alloy and adopting specific heat treatment and refining steps.
The preparation of high thermal conductivity Al-Si-based alloy materials is achieved, with thermal conductivity, tensile strength, yield strength and elongation reaching 195~205 W/(m·K), 260~310 MPa, 220~270 MPa and 8~10%, while reducing preparation costs.
Smart Images

Figure CN118756013B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lightweight high thermal conductivity metal materials, and in particular relates to a high thermal conductivity Al-Si based alloy material and a preparation method thereof. Background Art
[0002] With the continuous development of science and technology in my country, especially the rapid development of the electronic communications industry represented by 5G technology and the upgrading of products, products are developing towards miniaturization, lightweight, and structural-functional integration. Compared with 4G, the new generation of 5G products has a higher degree of integration, a more complex structure, and a significantly greater difficulty in production. In addition, due to the doubling of the number of transceiver channels, the power has increased sharply, and the heat generation has also increased significantly. It is reported that for every 1°C increase in the operating temperature of semiconductor components, their reliability decreases by 5%. High-power integrated circuit equipment cannot dissipate heat in time, heat accumulates and the temperature rises rapidly, and the probability of failure of electronic equipment will increase significantly. In order to ensure the service life and working stability of high-end equipment in the fields of electronic communications, strict requirements are placed on the thermal conductivity of the product shell material.
[0003] Al-Si alloy has good fluidity and specific strength, as well as a low expansion coefficient, and is widely used in the casting production of complex thin-walled heat dissipation shells. Patent (CN115537611B) and patent (CN117127062A) both disclose a high thermal conductivity and low expansion Al-Si-Ni based alloy and its preparation method. The former discloses an alloy composition of 20~30% Si, 10~20% Ni, 1~3% Cu, 0~1% Mg, 0.1~0.3% P and the balance Al (mass percentage, the same below), and the latter discloses an alloy composition of 15~25% Si, 15~20% Ni, 2~5% Cu, 0.1~0.5% Fe, 0.5~1.5% Mg, 0.2~0.5% The preparation steps mainly include Al-Si-Ni alloy smelting, adding trace alloying elements, refining and P modification, casting and solidification molding, heat treatment at 510-530℃ for 6-8h and 210-230℃ for 8-12h, etc., and the thermal conductivity and expansion coefficient can reach 100-120W / m·K and 10-11.5×10 -6 / K Al-Si-Ni based alloy.
[0004] The patent (CN117363934A) discloses a low-titanium and low-vanadium hypoeutectic high thermal conductivity Al-Si alloy material and its preparation method. The alloy composition is 6.5~8.5% Si, 0.65~0.8% Fe, 0.05~0.15% Mg, 0.008~0.02% Sr, 0.01~0.05% RE, 0.008~0.015% B, V<0.002%, Ti<0.001%, the total amount of other impurity elements does not exceed 0.15%, and the balance is Al. The preparation method includes: feeding and smelting, composition adjustment, refining and adding Al-B master alloy boronization treatment, liquid conversion and adding Mg and Al-Sr-RE modifiers, secondary refining and casting molding, etc. The thermal conductivity, tensile strength and elongation of the alloy can reach 180 W / (m·K), 240 MPa and 14% respectively.
[0005] The patent (CN113802036A) discloses a high thermal conductivity and high elongation cast Al-Si alloy material and its preparation method. The alloy composition is 9.5~11.5% Si, 0.5~0.8% Mn, 0.1~0.5% Mg, 0.04~0.15% Ti, 0.02-0.04% Ce, 0.04~0.06% Sr, and the rest is Al. The preparation method includes the steps of drying, smelting, Sr and Ce modification, refining and casting. The thermal conductivity, tensile strength and elongation of the material can reach 181.68 W / (m·K), 228.94 MPa and 14.62% respectively.
[0006] The patent (CN117448633A) discloses a high thermal conductivity Al-Si alloy and a preparation method thereof. The alloy composition is 4.5~6.5% Si, 0~1.0% Zn, 0~0.4% Mg, 0~1.0% Cu, 0.5~1.2% Fe, 0~0.3% Co, 0.02~0.2% Sr, 0.02~0.15% B, 0.05~0.25% RE, and the rest is Al. The preparation method includes the steps of material preparation, temperature melting, refining and modification, transportation and degassing, vacuum high-pressure die casting, 500~550℃ insulation for 2~12h, 130~200℃ aging for 2~12h, and 180~300℃ annealing for 1~3h. The thermal conductivity, tensile strength and elongation of the material are 183.4 W / (m·K), 243 MPa and 13.2% respectively.
[0007] In addition, the paper (Qiu Jin, Cao Yangjing, Luo Xiaomei, et al. Effect of A356 aluminum alloy squeeze casting solidification process and heat treatment on its properties. Special Casting and Nonferrous Alloys, 2024, 44(2): 189-197) reported that the semi-solid squeeze casting A356 aluminum alloy sample with alloy composition (mass percentage) of 7.06% Si, 0.27% Mg, 0.115% Fe, 0.097% Ti, 0.001% Cu, 0.01% Zn, and the balance Al was treated with solid solution at 540℃ for 4h and aging at 180℃ for 9h. Its thermal conductivity, tensile strength and elongation were 191.82W / (m·K), 283.65 MPa and 13.2%, respectively. The paper (Xiao Yuehui, Cheng Yongqi, Chen Yuhang, et al. Effect of Sm on the mechanical and thermal conductivity of Sr / B composite modified A356 aluminum alloy. Hot Working Technology, 2022, 51(19):55-59) reported that the thermal conductivity, tensile strength and elongation of the modified cast commercial A356 aluminum alloy can reach 159W / (m·K), 203.7 MPa and 8.4%, respectively. The paper (Qi Zhongyi, Wang Bo, Jiang Hongxiang, Zhang Lili, He Jie. Effect of trace rare earth La on the microstructure and properties of Al-7%Si-0.6Fe alloy, Acta Physica Sinica, 2024, 73(7):076401) studied the influence of composite modification of trace rare earth La and elements Sr and B on the microstructure and thermal conductivity of Al-Si-Fe based alloy. Thesis (Ding Yuming. Study on the influence of aging treatment on thermal conductivity and mechanical properties of composite refined modified A356 aluminum alloy. Hebei University of Technology, 2022.5) shows that the thermal conductivity, tensile strength and elongation of A356 alloy can reach 188.44W / (m·K), 286 MPa and 10.5% respectively after high temperature pre-aging at 490℃ for 80.5min and secondary aging at 190℃ for 6h. Thesis (Xiao Yuehui. Study on the influence of composite treatment on thermal conductivity and properties of A356 aluminum alloy. Guangdong University of Technology, 2021.5) shows that after Sr / B composite modification and low temperature aging treatment at 200℃ for 10h, the thermal conductivity, tensile strength and elongation of A356 aluminum alloy can reach 184.6W / (m·K), 180.5 MPa and 3.2% respectively.
[0008] The above Al-Si based aluminum alloys have their own advantages and disadvantages in terms of material preparation methods. They are generally complicated to operate, have a long preparation cycle, low efficiency, and an inverted relationship between the strength and thermal conductivity of aluminum alloy materials, resulting in insufficient comprehensive performance of the materials. The appropriate addition of alloying elements is relatively simple, clean and efficient in synergizing the mechanical properties and thermal conductivity of aluminum alloys. With the continuous development of the aluminum industry and the increasing requirements for aluminum alloy performance, preparation cost and cycle, it is urgent to develop new methods and technologies in terms of raw material sources and preparation efficiency. Summary of the invention
[0009] The purpose of the present invention is to provide a high thermal conductivity Al-Si based alloy material and a preparation method thereof, so as to meet the urgent demand for high thermal conductivity Al-Si based alloy materials in high technology fields such as electronic communications. The alloy has better thermal conductivity and mechanical properties and low cost advantages than the existing commercial Al-Si based alloys.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] A high thermal conductivity Al-Si based alloy material comprises the following components by weight percentage: 6.5-9.5% silicon, 0-0.65% magnesium, 0-0.6% iron, 0.02-0.1% strontium, 0.01-0.1% boron, 0.02-0.2% lanthanum, 0.01-0.1% cerium, and the balance is aluminum.
[0012] The method for preparing the high thermal conductivity Al-Si based alloy material comprises the following steps:
[0013] (1) Prepare alloy raw materials according to component requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 740℃~770℃;
[0014] (2) adding silicon, iron and magnesium elements in the form of Al-Si, Al-Fe and Al-Mg master alloys, and stirring the alloy melt to obtain a uniform Al-Si alloy melt;
[0015] (3) introducing a refining agent and high-purity argon gas to perform refining and slag removal on the Al-Si alloy melt;
[0016] (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 700°C to 720°C, and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys;
[0017] (5) adding the recycled rare earth elements La and Ce recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and deslagging to obtain an Al-Si based alloy melt;
[0018] (6) pouring the Al-Si based alloy melt into a mold and cooling and solidifying it into an Al-Si based alloy ingot;
[0019] (7) The ingot is sequentially subjected to heat treatment at 475°C to 550°C for 0.2 to 2 h and water quenching, and double-stage aging treatment at 180°C to 350°C to obtain a high thermal conductivity Al-Si based alloy material.
[0020] In the method for preparing the high thermal conductivity Al-Si based alloy material, in step (3), the refining agent is composed of, by weight percentage: 46% sodium cryolite, 40% salt slag prepared by reacting fluoride salts to prepare Al5Ti1B master alloy, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar.
[0021] In the method for preparing the high thermal conductivity Al-Si based alloy material, in step (5), the rare earth elements La and Ce are added in the form of a regenerated rare earth La-Ce alloy obtained by phase separation-extraction-separation from LaFeSi magnetic refrigeration waste using metallic magnesium.
[0022] In the preparation method of the high thermal conductivity Al-Si based alloy material, in step (7), the short-time two-stage aging treatment at 180°C to 350°C is as follows: after keeping the temperature at 250°C to 350°C for 0.1 to 1.2 hours and cooling to room temperature with the furnace, the temperature is kept at 180°C to 200°C for 2 to 4 hours and cooling to room temperature with the furnace.
[0023] The principle of the present invention is as follows:
[0024] The high thermal conductivity Al-Si based alloy of the present invention is added with strontium, boron and rare earth elements lanthanum and cerium at the same time, and the performance of the Al-Si based alloy can be improved through the following mechanisms: 1) Sr can improve the thermal conductivity of the alloy by improving the morphology of the eutectic Si phase; B has no effect on the morphology of the eutectic Si, but can reduce the number of atoms of the solid-dissolved impurity elements Cr, V, etc. in the matrix Al through boriding, reduce the influence of lattice distortion, and thus improve the thermal conductivity of the aluminum alloy; rare earth La and cerium Ce can effectively improve the morphology of the eutectic Si phase and thus improve the thermal conductivity of the alloy. 2) When Sr and B coexist in the Al-Si based alloy, strontium boron (Sr, B) compounds will be generated, so that the modification effect of Sr becomes worse, that is, there is a poisoning effect between Sr and B. Adding trace amounts of rare earth La and Ce can react with B preferentially to generate (La, B) compounds to neutralize the poisoning effect of the simultaneous addition of Sr and B on the modification effect of the eutectic Si, thereby improving the modification effect of the eutectic Si phase. The more expensive elements in the Al-Si based alloy of the present invention are rare earth elements. In order to reduce costs, rare earth elements La, Ce and element Mg are added in the form of a recycled Mg-La-Ce alloy obtained by extracting and separating LaFeSi magnetic refrigeration waste with magnesium, which is conducive to the reuse of secondary metal resources and promotes the development of a green, low-carbon, circular economy.
[0025] In addition, in the preparation process of the high thermal conductivity Al-Si based alloy material of the present invention, after obtaining the Al-Si based alloy ingot, it is subjected to a high temperature heat treatment at 475°C to 550°C to promote the melting and spheroidization of the eutectic Si phase, thereby reducing the scattering of electrons by the coarse eutectic Si and improving the thermal conductivity of the Al-Si based alloy. Subsequently, the Al-Si based alloy material after the high temperature heat treatment and quenching treatment is subjected to a short-term two-stage aging treatment at 180°C to 350°C: 250°C to 350°C for 0.1 to 1.2 hours and 180°C to 200°C for 2 to 4 hours. In this way, on the one hand, the precipitation of the solid solution Si element in the α-Al matrix is promoted, thereby reducing the scattering effect of the solid solution atoms on electrons; on the other hand, the solid solution Mg and Si elements in the α-Al matrix are promoted to precipitate in the form of nano-scale magnesium silicon (Mg, Si) phase, thereby improving the mechanical properties of the Al-Si based alloy.
[0026] The advantages and beneficial effects of the present invention are as follows:
[0027] The high thermal conductivity Al-Si based alloy material prepared by the present invention has excellent thermal conductivity, and its thermal conductivity, tensile strength, yield strength and elongation can reach 195-205 W / (m·K), 260-310 MPa, 220-270 MPa and 8-10% respectively. Rare earth elements La and Ce are added in the form of recycled rare earth La-Ce alloy obtained by extracting and separating LaFeSi magnetic refrigeration waste with magnesium, which is conducive to the reuse of secondary metal resources and cost reduction, and promotes the development of green low-carbon circular economy. The preparation of high-quality aluminum alloy materials with excellent mechanical properties and electrical conductivity in a short cycle and at low cost has significant benefits for promoting the development of high-end electronic communications such as 5G, as well as economic resources and social environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The microstructure of the Al-Si based alloy ingot prepared according to the method of Example 1 is shown in FIG.
[0029] Figure 2 The microstructure of the Al-Si based alloy prepared according to the method of Example 2 is shown in FIG.
[0030] Figure 3 The microstructure of the Al matrix in the Al-Si based alloy prepared according to the method of Example 3.
[0031] Figure 4 The microstructure of the Al-Si based alloy prepared according to the method of Example 4 is shown in FIG.
[0032] Figure 5 The microstructure of the Al matrix in the Al-Si based alloy prepared according to the method of Example 5.
[0033] Figure 6The microstructure of the Al matrix in the Al-Si based alloy prepared according to the method of Example 6. DETAILED DESCRIPTION
[0034] In a specific implementation process, the high thermal conductivity Al-Si based alloy material of the present invention is composed of the following elements in weight percentage: 6.5-9.5% silicon, 0-0.65% magnesium, 0-0.6% iron, 0.02-0.1% strontium, 0.01-0.1% boron, 0.02-0.2% lanthanum, 0.01-0.1% cerium, and the balance is aluminum. Preferably, 6.5-7.5% silicon, 0.3-0.5% magnesium, 0.2-0.3% iron, 0.02-0.05% strontium, 0.02-0.05% boron, 0.02-0.05% lanthanum, 0.01-0.03% cerium, and the balance is aluminum. The preparation method of the high thermal conductivity Al-Si based alloy material is as follows: prepare the alloy raw materials according to the above-mentioned component requirements, melt the aluminum ingot → add silicon, iron, magnesium and other elements and fully stir the melt to obtain an Al-Si-Fe alloy melt → refine and purify the Al-Si-Fe alloy melt → add strontium and boron into the alloy melt in the form of an intermediate alloy and fully stir and keep warm → add rare earth elements lanthanum and cerium into the alloy melt in the form of a recycled rare earth La-Ce alloy obtained from LaFeSi magnetic refrigeration waste and fully stir and keep warm → pour the alloy melt into a mold after slagging and cool and solidify to obtain an Al-Si based alloy ingot → sequentially perform water quenching treatment after keeping warm at 475°C~550°C for 0.2~2h, heat treatment at 250°C~350°C for 0.1~1.2h and heat treatment at 180°C~200°C for 2~4h.
[0035] Among them, the rare earth elements La and Ce are added in the form of a recycled rare earth La-Ce alloy obtained by phase separation-extraction-separation from LaFeSi magnetic refrigeration waste using metal magnesium. LaFeSi magnetic refrigeration waste is waste of lanthanum iron silicon-based magnetic refrigeration alloy, and its main components and contents are as follows: by mass percentage, lanthanum 14.8%, cerium 3.32%, iron 77.4%, silicon 4.48%. The specific process and process parameters of the recycled rare earth La-Ce alloy obtained by phase separation-extraction-separation of metal magnesium are as follows:
[0036] In the first step, the LaFeSi magnetic refrigeration waste is sequentially surface cleaned, dried, and crushed to obtain waste particles with an effective diameter of no more than 3 mm;
[0037] In the second step, the waste particles were placed in a magnesium melt at 900°C under argon protection, kept warm and stirred for 35 minutes, and then the temperature was reduced to 800°C and allowed to stand for 20 minutes.
[0038] The third step is to pour the upper layer of magnesium melt containing rare earth elements such as La and Ce into the mold to form a Mg-La-Ce based master alloy.
[0039] In the fourth step, the Mg-La-Ce based master alloy is placed in a vacuum distillation furnace and heated to 1100° C. for distillation for 30 min, and then the recovered La-Ce alloy is obtained.
[0040] In addition, the salt slag of Al5Ti1B master alloy prepared by fluoride salt reaction has the following main components and contents: by mass percentage, 60%~90% potassium fluoroaluminate, 0%~24% potassium fluoride, 0%~27% aluminum fluoride, and 0~6% magnesium fluoride.
[0041] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope and application scope of the present invention are not limited to the following embodiments. Example 1
[0042] In this embodiment, the formula ratio of the high thermal conductivity Al-Si based alloy material is as follows, by weight percentage: 7.0% silicon, 0.6% iron, 0.02% strontium, 0.024% boron, 0.02% rare earth element lanthanum, 0.01% cerium, and the balance is aluminum.
[0043] In this embodiment, the preparation method of the high thermal conductivity Al-Si based alloy material comprises the following steps:
[0044] (1) Prepare alloy raw materials according to composition requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 740°C;
[0045] (2) adding silicon and iron elements in the form of Al-Si and Al-Fe master alloys, and stirring the alloy melt to obtain a uniform Al-Si-Fe alloy melt;
[0046] (3) introducing a refining agent (in terms of weight percentage, the composition of which is 46% sodium cryolite, 40% salt slag for preparing Al5Ti1B master alloy by fluoride salt reaction, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar) and high-purity argon gas (volume concentration of 99.999%) into the Al-Si-Fe alloy melt for refining and slag removal;
[0047] (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 720° C., and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys;
[0048] (5) adding the recycled rare earth La-Ce alloy recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and slagging to obtain an Al-Si based alloy melt;
[0049] (6) The Al-Si based alloy melt is poured into a mold and cooled and solidified into an Al-Si based alloy ingot.
[0050] like Figure 1 As shown, the cast microstructure of the high thermal conductivity Al-Si based alloy material prepared in this embodiment, the light grey in the figure is the Si phase, and the dark grey is the Al matrix. Usually, the eutectic Si in the cast structure of the binary Al-Si alloy is in the form of coarse long needles, rods and blocks, with a characteristic size of more than 10 μm. Example 1 Compared with the conventional cast binary Al-Si alloy structure, the eutectic Si in the Al-Si based alloy ingot prepared by the method described in Example 1 has been effectively modified. The thermal conductivity, tensile strength, yield strength and elongation of the Al-Si based alloy material can reach 171W / (m·K), 163 MPa, 74 MPa and 13.5%, respectively. Example 2
[0051] In this embodiment, the formula ratio of the high thermal conductivity Al-Si based alloy material is as follows, by weight percentage: 7.0% silicon, 0.25% iron, 0.02% strontium, 0.024% boron, 0.02% rare earth element lanthanum, 0.01% cerium, and the balance is aluminum.
[0052] In this embodiment, the preparation method of the high thermal conductivity Al-Si based alloy material comprises the following steps:
[0053] (1) Prepare alloy raw materials according to composition requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 740°C;
[0054] (2) adding silicon and iron elements in the form of Al-Si and Al-Fe master alloys, and stirring the alloy melt to obtain a uniform Al-Si-Fe alloy melt;
[0055] (3) introducing a refining agent (in terms of weight percentage, the composition of which is 46% sodium cryolite, 40% salt slag for preparing Al5Ti1B master alloy by fluoride salt reaction, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar) and high-purity argon gas (volume concentration of 99.999%) into the Al-Si-Fe alloy melt for refining and slag removal;
[0056] (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 720° C., and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys;
[0057] (5) adding the recycled rare earth La-Ce alloy recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and slagging to obtain an Al-Si based alloy melt;
[0058] (6) pouring the Al-Si based alloy melt into a mold and cooling and solidifying it into an Al-Si based alloy ingot;
[0059] (7) The aluminum alloy ingot was kept at 530°C for 0.5 h and then water quenched.
[0060] like Figure 2 As shown in the figure, the microstructure of the high thermal conductivity Al-Si based alloy material is prepared in this embodiment. Compared with Example 1, the eutectic Si in the Al-Si based alloy ingot prepared by the method described in Example 2 is further spheroidized after being kept at 530°C for 0.5h. The thermal conductivity, tensile strength, yield strength and elongation of the Al-Si based alloy material can reach 183 W / (m·K), 193 MPa, 104 MPa and 12.4% respectively. Compared with Example 1, it is shown that the thermal conductivity and mechanical properties can be improved by water quenching the aluminum alloy ingot after keeping it at 530°C for 0.5h. Example 3
[0061] In this embodiment, the formula ratio of the high thermal conductivity Al-Si based alloy material is as follows, by weight percentage: 7.0% silicon, 0.4% magnesium, 0.25% iron, 0.02% strontium, 0.024% boron, 0.02% rare earth element lanthanum, 0.01% cerium, and the balance is aluminum.
[0062] In this embodiment, the preparation method of the high thermal conductivity Al-Si based alloy material comprises the following steps:
[0063] (1) Prepare alloy raw materials according to composition requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 740°C;
[0064] (2) adding silicon, iron and magnesium elements in the form of Al-Si, Al-Fe and Al-Mg master alloys, and stirring the alloy melt to obtain a uniform Al-Si-Fe-Mg alloy melt;
[0065] (3) introducing a refining agent (in terms of weight percentage, the composition of which is 46% sodium cryolite, 40% salt slag for preparing Al5Ti1B master alloy by fluoride salt reaction, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar) and high-purity argon gas (volume concentration of 99.999%) into the Al-Si-Fe-Mg alloy melt for refining and slag removal;
[0066] (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 720° C., and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys;
[0067] (5) adding the recycled rare earth La-Ce alloy recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and slagging to obtain an Al-Si based alloy melt;
[0068] (6) pouring the Al-Si based alloy melt into a mold and cooling and solidifying it into an Al-Si based alloy ingot;
[0069] (7) The ingot is sequentially subjected to heat treatment at 530°C for 0.5 h and water quenching, and heat treatment at 180°C for 4 h to obtain a high thermal conductivity Al-Si based alloy material.
[0070] like Figure 3 As shown, the microstructure of the high thermal conductivity Al-Si based alloy material prepared in this embodiment, heat treatment at 180°C for 4 hours promoted the precipitation of the black (Mg, Si) phase in the matrix Al. Example 3 Compared with Example 2, the morphology of eutectic Si in the Al-Si based alloy ingot prepared by the method described in Example 3 did not change much. The thermal conductivity, tensile strength, yield strength and elongation of the Al-Si based alloy material can reach 181 W / (m·K), 238 MPa, 174 MPa and 11.5%, respectively. Compared with Example 2, it is shown that the mechanical properties can be improved by adding an appropriate amount of magnesium and heat treatment at 180°C for 4 hours. Example 4
[0071] In this embodiment, the formula ratio of the high thermal conductivity Al-Si based alloy material is as follows, by weight percentage: 7.0% silicon, 0.4% magnesium, 0.25% iron, 0.02% strontium, 0.024% boron, 0.02% rare earth element lanthanum, 0.01% cerium, and the balance is aluminum.
[0072] In this embodiment, the preparation method of the high thermal conductivity Al-Si based alloy material comprises the following steps:
[0073] (1) Prepare alloy raw materials according to composition requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 750°C;
[0074] (2) adding silicon, iron and magnesium elements in the form of Al-Si, Al-Fe and Al-Mg master alloys, and stirring the alloy melt to obtain a uniform Al-Si-Fe-Mg alloy melt;
[0075] (3) introducing a refining agent (in terms of weight percentage, the composition of which is 46% sodium cryolite, 40% salt slag for preparing Al5Ti1B master alloy by fluoride salt reaction, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar) and high-purity argon gas (volume concentration of 99.999%) into the Al-Si-Fe-Mg alloy melt for refining and slag removal;
[0076] (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 720° C., and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys;
[0077] (5) adding the recycled rare earth La-Ce alloy recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and slagging to obtain an Al-Si based alloy melt;
[0078] (6) pouring the Al-Si based alloy melt into a mold and cooling and solidifying it into an Al-Si based alloy ingot;
[0079] (7) The ingot is sequentially subjected to heat treatment at 475°C for 2 h and water quenching, and heat treatment at 300°C for 0.7 h to obtain a high thermal conductivity Al-Si based alloy material.
[0080] like Figure 4 As shown, the microstructure of the high thermal conductivity Al-Si based alloy material prepared in this embodiment, and the heat treatment at 300°C for 0.7h promoted the precipitation of Si solute in the matrix Al. Compared with Example 3, the morphology of eutectic Si in the Al-Si based alloy ingot prepared by the method described in Example 4 did not change much. The thermal conductivity, tensile strength, yield strength and elongation of the Al-Si based alloy material can reach 194.2 W / (m·K), 212 MPa, 131 MPa and 11.8% respectively. Compared with Example 3, it is shown that the heat treatment at 300°C for 0.7h can improve the thermal conductivity. Example 5
[0081] In this embodiment, the formula ratio of the high thermal conductivity Al-Si based alloy material is as follows, by weight percentage: 7.0% silicon, 0.4% magnesium, 0.25% iron, 0.02% strontium, 0.024% boron, 0.02% rare earth element lanthanum, 0.01% cerium, and the balance is aluminum.
[0082] In this embodiment, the preparation method of the high thermal conductivity Al-Si based alloy material comprises the following steps:
[0083] (1) Prepare alloy raw materials according to composition requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 760°C;
[0084] (2) adding silicon, iron and magnesium elements in the form of Al-Si, Al-Fe and Al-Mg master alloys, and stirring the alloy melt to obtain a uniform Al-Si-Fe-Mg alloy melt;
[0085] (3) introducing a refining agent (in terms of weight percentage, the composition of which is 46% sodium cryolite, 40% salt slag for preparing Al5Ti1B master alloy by fluoride salt reaction, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar) and high-purity argon gas (volume concentration of 99.999%) into the Al-Si-Fe-Mg alloy melt for refining and slag removal;
[0086] (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 700° C., and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys;
[0087] (5) adding the recycled rare earth La-Ce alloy recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and slagging to obtain an Al-Si based alloy melt;
[0088] (6) pouring the Al-Si based alloy melt into a mold and cooling and solidifying it into an Al-Si based alloy ingot;
[0089] (7) The ingot was sequentially subjected to heat treatment at 550°C for 0.2 h and water quenching, and then subjected to furnace cooling to room temperature at 300°C for 0.7 h, and then subjected to furnace cooling to room temperature at 180°C for 4 h, thereby obtaining a high thermal conductivity Al-Si based alloy material.
[0090] like Figure 5 As shown, the microstructure of the high thermal conductivity Al-Si based alloy material is prepared in this embodiment, and the double-stage heat treatment at 300°C for 0.7h and 180°C for 4h promotes the precipitation of Si solute and (Mg, Si) strengthening phase in the matrix Al. Compared with Example 4, the morphology of eutectic Si in the Al-Si based alloy ingot prepared by the method described in Example 5 does not change much. The thermal conductivity, tensile strength, yield strength and elongation of the Al-Si based alloy material can reach 197.6 W / (m·K), 267MPa, 224MPa and 9.3%, respectively. Compared with Example 3 and Example 4, it is shown that the double-stage short-time aging improves the thermal conductivity and mechanical properties at the same time. Example 6
[0091] In this embodiment, the formula ratio of the high thermal conductivity Al-Si based alloy material is as follows, by weight percentage: 7.0% silicon, 0.4% magnesium, 0.25% iron, 0.02% strontium, 0.024% boron, 0.04% rare earth element lanthanum, 0.02% cerium, and the balance is aluminum.
[0092] In this embodiment, the preparation method of the high thermal conductivity Al-Si based alloy material comprises the following steps:
[0093] (1) Prepare alloy raw materials according to composition requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 770°C;
[0094] (2) adding silicon, iron and magnesium elements in the form of Al-Si, Al-Fe and Al-Mg master alloys, and stirring the alloy melt to obtain a uniform Al-Si-Fe-Mg alloy melt;
[0095] (3) introducing a refining agent (in terms of weight percentage, the composition of which is 46% sodium cryolite, 40% salt slag for preparing Al5Ti1B master alloy by fluoride salt reaction, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar) and high-purity argon gas (volume concentration of 99.999%) into the Al-Si-Fe-Mg alloy melt for refining and slag removal;
[0096] (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 710° C., and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys;
[0097] (5) adding the recycled rare earth La-Ce alloy recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and slagging to obtain an Al-Si based alloy melt;
[0098] (6) pouring the Al-Si based alloy melt into a mold and cooling and solidifying it into an Al-Si based alloy ingot;
[0099] (7) The ingot is sequentially subjected to heat treatment at 500°C for 1 h and water quenching, and is then subjected to furnace cooling at 350°C for 0.1 h and then furnace cooling to room temperature, and is then subjected to furnace cooling at 200°C for 2 h to obtain a high thermal conductivity Al-Si based alloy material.
[0100] like Figure 6 As shown, the microstructure of the high thermal conductivity Al-Si based alloy material prepared in this embodiment promotes the further precipitation of Si and Mg atoms in the Al matrix after optimizing the addition amount of recycled rare earth elements La and Ce, so that the thermal conductivity and mechanical properties are further comprehensively improved. Example 6 Compared with Example 5, the morphology of eutectic Si in the Al-Si based alloy ingot prepared by the method described in Example 6 does not change much. The thermal conductivity, tensile strength, yield strength and elongation of the Al-Si based alloy material can reach 202 W / (m·K), 305 MPa, 261 MPa and 8.4%, respectively. Compared with Example 5, it is shown that optimizing the addition amount of recycled rare earth elements La and Ce can further improve the thermal conductivity and mechanical properties.
[0101] The implementation results show that the Al-Si based alloy material prepared by the present invention has the characteristics of low cost, excellent comprehensive performance, etc.
Claims
1. A high thermal conductivity Al-Si based alloy material, characterized in that: The Al-Si based alloy material comprises the following components by weight percentage: 6.5-7.5% silicon, 0.3-0.5% magnesium, 0.2-0.3% iron, 0.02-0.05% strontium, 0.02-0.05% boron, 0.02-0.05% lanthanum, 0.01-0.03% cerium, and the balance is aluminum; The rare earth elements lanthanum and cerium are added in the form of a recycled rare earth La-Ce alloy obtained by phase separation-extraction-separation from LaFeSi magnetic refrigeration waste using metallic magnesium. The LaFeSi magnetic refrigeration waste is a waste of lanthanum iron silicon-based magnetic refrigeration alloy, and its composition and content are as follows: by mass percentage, lanthanum 14.8%, cerium 3.32%, iron 77.4%, silicon 4.48%; The specific process and process parameters of the recycled rare earth La-Ce alloy obtained by metal magnesium phase separation-extraction-separation are as follows: In the first step, the LaFeSi magnetic refrigeration waste is sequentially surface cleaned, dried, and crushed to obtain waste particles with an effective diameter of no more than 3 mm; In the second step, the waste particles were placed in a magnesium melt at 900°C under argon protection, kept warm and stirred for 35 min, then the temperature was reduced to 800°C and left to stand for 20 min; The third step is to pour the upper layer of magnesium melt containing rare earth elements lanthanum and cerium into a mold to form a Mg-La-Ce based master alloy; In the fourth step, the Mg-La-Ce based master alloy is placed in a vacuum distillation furnace and heated to 1100° C. for distillation for 30 min, and then the recovered La-Ce alloy is obtained.
2. The method for preparing a high thermal conductivity Al-Si based alloy material according to claim 1, characterized in that: The steps include: (1) Prepare alloy raw materials according to component requirements, heat and melt pure aluminum ingots, and keep the melt temperature at 740℃~770℃; (2) adding silicon, iron and magnesium elements in the form of Al-Si, Al-Fe and Al-Mg master alloys, and stirring the alloy melt to obtain a uniform Al-Si alloy melt; (3) introducing a refining agent and high-purity argon gas to perform refining and slag removal on the Al-Si alloy melt; (4) adjusting the temperature of the aluminum alloy melt after the treatment in step (3) to 700°C to 720°C, and adding strontium and boron elements in the form of Al-Sr and Al-B master alloys; (5) adding recycled rare earth elements La and Ce recovered from LaFeSi magnetic refrigeration waste to the alloy melt treated in step (4), stirring and deslagging to obtain an Al-Si based alloy melt; (6) pouring the Al-Si based alloy melt into a mold and cooling and solidifying it into an Al-Si based alloy ingot; (7) The ingot is sequentially subjected to heat treatment at 475°C to 550°C for 0.2 to 2 h and water quenching, and double-stage aging treatment at 180°C to 350°C to obtain a high thermal conductivity Al-Si based alloy material; In step (7), the short-term two-stage aging treatment at 180°C-350°C is as follows: after keeping at 250°C-350°C for 0.1-1.2 hours and cooling to room temperature with the furnace, keeping at 180°C-200°C for 2-4 hours and cooling to room temperature with the furnace.
3. The method for preparing a high thermal conductivity Al-Si based alloy material according to claim 2, characterized in that: In step (3), the refining agent is composed of 46% sodium cryolite, 40% salt slag prepared from fluoride salt reaction to prepare Al5Ti1B master alloy, 8% aluminum fluoride, 3% calcium fluoride, and 3% potassium feldspar, by weight percentage.
Citation Information
Patent Citations
High-thermal-conductivity and high-elongation cast Al-Si alloy material and preparation method thereof
CN113802036A
A high thermal conductivity, low expansion Al-Si-Ni based alloy and its preparation method
CN115537611B
High-thermal-conductivity low-expansion Al-Si-Ni-based alloy and preparation method thereof
CN117127062A
Low-titanium and low-vanadium hypoeutectic high-thermal-conductivity Al-Si alloy material and preparation method thereof
CN117363934A
High-thermal-conductivity Al-Si alloy and preparation method thereof
CN117448633A